Use genetic algorithm to determine optimal weights of integrated operation in fuzzycontrol method using hedge algebras. - Hồ, Nguyễn Cát; Hà, Phạm Thanh; Lân, Vũ Như (Journal of Computer Science and Cybernetics, 2012)
-